Influence of operator's experience on complications of root canal treatment using contemporary techniques: a retrospective study - Tongfei Shao; Rui Guan; Chen Zhang; Benxiang Hou (BMC, 2024)
Abstract Background Endodontic treatment has benefited from the development of new techniques and equipment. Few clinical studies have been published on the complications associated with root canal preparations performed by doctors with different working experiences using contemporary techniques. This study aimed to analyze the complications of endodontic treatment performed by residents and endodontic specialists in a teaching stomatology hospital using contemporary techniques. Methods Cases of root canal treatment (RCT) and non-surgical root canal retreatment (ReRCT) performed by residents with 1-3 years of experience and endodontic specialists with 5-7 years of experience were collected from the electronic medical system of the Department of Endodontics, Beijing Stomatology Hospital, from September 1, 2020 to August 31, 2021. The cases were examined in terms of patient age, sex, type of tooth, diagnosis, treatment modality (RCT or ReRCT), number of appointments, whether an operating microscope was used, presence of ledges, canal transportation, perforations, missed canals, separated instruments, flare-ups and clinical incidence of second mesiobuccal (MB2) root canal in the maxillary molars. Results In total, 859 teeth from 820 patients were included in the analysis. The overall incidence of complications in the resident group was significantly higher than that in the specialist group. More ledges and flare-ups were observed in the resident group (p < 0.05). The clinical incidence of MB2 was significantly higher in the specialist group (p < 0.05). There were no significant differences in root canal transportation, perforation, or instrument separation between the two groups (p < 0.05). Multivariate analysis showed that the incidence of root canal preparation complications was related to operator experience, tooth type and treatment modality. Conclusions Technical advancements could reduce the effect of working experience on RCT complications between residents and endodontic specialists in a teaching stomatology hospital.